2012
DOI: 10.1016/j.agee.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of songbird productivity at a restored gravel pit: Influence of seasonal flooding and rainfall patterns and implications for habitat management

Abstract: The restoration of riparian sites following aggregate extraction frequently aims to expand the wetland habitat, and enhance the wetland wildlife community. However, aggregate extraction sites, typically on river flood plains, are subject to unpredictable flooding along with climate variability and other factors beyond the control of local management that may be equally important in determining the success or failure of a restoration project. Here we report on an 18 year study tracking songbird productivity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…), European Pied Flycatcher Ficedula hypoleuca (Both et al . ), Eurasian Reed Warbler Acrocephalus scirpaceus (Harrison & Whitehouse ) and Garden Warbler Sylvia borin (Widmer ). In contrast, only one study showed the dominance of wintering conditions on local population dynamics, in Northern Wheatear Oenanthe oenanthe (Arlt et al .…”
Section: The Serial Residency Hypothesismentioning
confidence: 99%
“…), European Pied Flycatcher Ficedula hypoleuca (Both et al . ), Eurasian Reed Warbler Acrocephalus scirpaceus (Harrison & Whitehouse ) and Garden Warbler Sylvia borin (Widmer ). In contrast, only one study showed the dominance of wintering conditions on local population dynamics, in Northern Wheatear Oenanthe oenanthe (Arlt et al .…”
Section: The Serial Residency Hypothesismentioning
confidence: 99%
“…Likewise, the conversion of wetlands into agricultural areas and human settlements poses a significant threat to waterbirds. Other than direct habitat loss, such change in the wetland landscape also affects hydrological systems (Harrison & Whitehouse, 2012), and consequently, habitat use by the waterbirds (Cintra, 2015; Tavares et al., 2015). Therefore, understanding how different environmental variables affect waterbirds is important for the effective conservation of waterbirds and the management of their habitats.…”
Section: Introductionmentioning
confidence: 99%
“…However, variations of rainfall and temperature that influence vegetation are among the many factors affecting wildlife habitats [4,5]. Yet, other site factors, including soil features, slope, and altitude, are of significant importance in determining vegetation attributes [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%